Deforestation, declining rainfall and drought in West Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Since the turn of the century up to 90% of the once extensive belt of coastal rainforests in West Africa has been cleared for farming, mining and the timber industry. A new study has now revealed that this destruction of rainforests may have caused...